Improving the Efficiency of the National Healthcare as Oriented Sustainable System. The Socio-Economic Aspects and Environmental Issues - SMAILOV, Bakhytzhan; ANDAROVA, Roza; AKYBAYEVA, Gulvira; GORDEYEVA, Yelena; MAMBETOVA, Sagynysh; GELASHVILI, Nikolay (Journal of Environmental Management and Tourism; Vol 13 No 5 (2022): JEMT, Volume XIII, Issue 5(61), Fall 2022DO - 10.14505/jemt.v13.5(61).18, 2022)
Based on a review of existing approaches, the article substantiates the nature of medical services as a mixed public good in relation with the sustainability of our society. In this regard, the typology of the modern healthcare sector is investigated on the basis of detailing the theoretical constructs underlying the applied models in response to their organizational mechanism. It is established that the target of all applied models of organization of the healthcare system is to search for optimal productivity. Medical efficiency of healthcare generates organizational effectiveness of therapeutic measures, social efficiency – the accessibility to medical services, economic efficiency – resource efficiency, environmental efficiency – overall sustainability of the healthcare system. The findings of this research outline that the ideal model of the healthcare system, besides the fact that should have a high medical, social and economic efficiency, should also be an environmentally oriented sustainable system which will allow healthy life also for the next generations.